Fragiles : porcelain, glass & ceramics - Klanten, Robert (Gestalten, 2008)
"... an eclectic collection of contemporary work in porcelain, glass, and ceramics ... documents over one thousand striking artistic projects, experimental applications, and innovative industrial products made from these materials by both established and emerging design talents and artists. Inspired by Modernism, an ironic depiction of kitsch and an expanded repertoire of forms made possible by technological developments, these designers are translating their creative visions into unconventional objects." --back cover